The integration of green finance and logistics: implications for green industry transformation - Ling Dai; Decai Tang; Eugene Ray Atsi; Meiling Zhao; Hui Zhang; Yuehong Kong; Liang Zhang (Frontiers in Environmental Science)
Green finance (GF), as a critical policy tool for supporting green development, plays a pivotal role in directing capital flows toward low-carbon and environmentally friendly industries. This provides essential support for the green transformation (GT) of the logistics industry (LI). However, limited research exists on the regional GT of the LI from the perspective of GF and LI integration. To address this gap, this study develops an evaluation index system for the integration of GF and the LI, as well as a separate system for assessing the GT of the LI. Using panel data from 30 Chinese provinces spanning 2010 to 2022, the study employs the Super-SBM-Undesirable model and the coupling coordination degree model for evaluation and analysis. Additionally, a threshold effect model is applied to examine the nonlinear relationship between GF-LI integration and the GT of the LI, alongside a heterogeneity analysis to explore regional disparities. The findings reveal three key insights: (1) In recent years, the integration of GF and the LI in China has significantly improved, advancing from a mildly imbalanced stage to moderate and high levels of coordination. However, significant regional disparities in the level of integration persist. (2) The integration of GF and the LI has a significant positive effect on the GT of the regional LI, characterized by an S-shaped relationship. (3) The impact of GF-LI integration on the GT of the LI exhibits notable regional heterogeneity. Compared with existing research results, this study expands the application scope of GF, focusing on the GT of the LI, a fundamental service industry, and further verifies the universality of GF in promoting low-carbon devel-opment in different industries. In addition, current research on the GT of the LI mainly focuses on technological innovation, environmental regulation, and supply chain optimization, while there is less attention paid to how GF can promote the GT of the LI through industrial integration.